Characteristics of consecutive tsunamis and resulting tsunami behaviors in southern Taiwan induced by the Hengchun earthquake doublet on 26 December 2006 - A.-C. Cheng; A.-C. Cheng; A. Suppasri; A. Suppasri; K. Pakoksung; F. Imamura; F. Imamura (Natural Hazards and Earth System Sciences, 2023)
Consecutive ML 7.0 submarine earthquakes occurred offshore of the Hengchun Peninsula, Taiwan, on 26 December 2006. A small tsunami was generated and recorded at tide gauge stations. This important event attracted public interest, as it was generated by an earthquake doublet and produced a tsunami risk for Taiwan. This study analyzed tide gauge tsunami waveforms and numerical simulations to understand the source characteristics and resulting behaviors of tsunamis. The maximum wave heights at the three nearest stations were 0.08 m (Kaohsiung), 0.12 m (Dongkung), and 0.3 m (Houbihu), and only Houbihu recorded the first wave crest as the largest. The tsunami duration was 3.9 h at Dongkung and over 6 h at Kaohsiung and Houbihu. Spectral analyses detected dominant periodic components of spectral peaks on the tsunami waveforms. The period band from 13.6–23.1 min was identified as the tsunami source spectrum, and the approximate fault area for the consecutive tsunamis was estimated to be 800 km2, with central fault depths of 20 km (first earthquake, Mw 7.0) and 33 km (second earthquake, Mw 6.9). The focal mechanisms of the first earthquake, with a strike of 319∘, dip of 69∘, and rake of −102∘, and the second earthquake, with a strike of 151∘, dip of 48∘, and rake of 0∘, could successfully reproduce the observed tsunami waveforms. Numerical simulations suggested that the tsunami waves were coastally trapped on the south coast of Taiwan during the tsunami's passage. The trapped waves propagated along the coast as edge waves, which repeatedly reflected and refracted among the shelves, interfered with incoming incident wave, and resonated with the fundamental modes of the shelves, amplifying and continuing the tsunami wave oscillation. These results elucidated the generation and consequential behaviors of the 2006 tsunami in southern Taiwan, contributing essential information for tsunami warning and coastal emergency response in Taiwan to reduce disaster risk.